Sintetična metafizika - Bole, Andraž (Analiza: časopis za kritično misel, 2025)
Synthetic Metaphysics The following article considers the connection between computation and metaphysics from two points of view. The first embraces a historical overview of authors who made key theoretical contributions to the modern understanding of computation. The second view elaborates on the concept of “synthetic metaphysics” which speculates that computation is a generalised form of every possible metaphysics. Limits of computation are limits of metaphysics so its most developed form cannot be analytical.